The role of employee performance mediation on organizational performance - Efi Herawati; Syamsurijal Tan; Tona Aurora Lubis; M. Syurya Hidayat (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
This study aimed to analyze the effect of employee training and development, motivation, work environment, employee competence on employee performance, and organizational performance. This study also aims to analyze employee performance as a mediating variable on organizational performance. The method of this research used SEM-PLS analysis. This research used all civil servants employees in The Regional Technical Implementing Unit for Goods Quality and Certification Testing Center (UPTD BPSMB) of the Jambi Province, Indonesia. This research concluded that Organizational performance is influenced by motivation, employee competence, work environment, and employee performance. Training and development, motivation, and work environment affect employee performance. Training and development, employee competence, work environment affect organizational performance mediated by employee performance. However, the influence of motivation on organizational performance cannot be mediated by employee performance